Relevant Cash Flows Information for Engineering & Constructionâ€™ Companies Investors - Pogorelov, Yurii; Dubovaya, Valentina; Bilousova, Anastasia (International Journal of Engineering and Technology, 2018)
Purpose of the article is to analyze and improve approaches of making financial reports about cash flows to provide relevant cash flows information for Engineering & Constructionâ€™ companies existing and potential investors. There were such research approaches used as analysis of financial reports, rating method and empirical analysis on open data. There is a fact found about non-compliance by Biggest Global Engineering & Constructionâ€™ companies of IAS 7 about reporting cash flows from operating activities using the direct method found. It was suggested to make all parts of statement of cash flows by direct method. It is grounded by topicality of such cash flows information for existing and potential investors, including making them modeling cash flows. It is recommended to expand using some indicators such as Â«Net Cash Flows from Operating ActivitiesÂ», Â«Net Cash Flows from Investing ActivitiesÂ», and Â«Net Cash Flows from Financing ActivitiesÂ» and Â«Cash Flows Receipts as the most objective one for characterizing economical activity of entities while making Global Business ratings. It is suggested to continue researches in direction of analyzing the best practical approaches to make report of Cash Flows from Operating, Investing & Financing Activities to generalize the best international experience.Â Â